The evolution of dual meat and milk cattle husbandry in Linearbandkeramik societies - Gillis, Rosalind E; Kovačiková, Lenka; Bréhard, Stéphanie; Guthmann, Emilie; Vostrovská, Ivana; Nohálová, Hana; Arbogast, Rose-Marie; Domboróczki, László; Pechtl, Joachim; Anders, Alexandra; Marciniak, Arkadiusz; Tresset, Anne; et al. (Proceedings. Biological sciences, 2017)
Cattle dominate archaeozoological assemblages from the north-central Europe between the sixth and fifth millennium BC and are frequently considered as exclusively used for their meat. Dairy products may have played a greater role than previously believed. Selective pressure on the lactase persistence mutation has been modelled to have begun between 6000 and 4000 years ago in central Europe. The discovery of milk lipids in late sixth millennium ceramic sieves in Poland may reflect an isolated regional peculiarity for cheese making or may signify more generalized milk exploitation in north-central Europe during the Early Neolithic. To investigate these issues, we analysed the mortality profiles based on age-at-death analysis of cattle tooth eruption, wear and replacement from 19 archaeological sites of the Linearbandkeramik (LBK) culture (sixth to fifth millennium BC). The results indicate that cattle husbandry was similar across time and space in the LBK culture with a degree of specialization for meat exploitation in some areas. Statistical comparison with reference age-at-death profiles indicate that mixed husbandry (milk and meat) was practised, with mature animals being kept. The analysis provides a unique insight into LBK cattle husbandry and how it evolved in later cultures in central and western Europe. It also opens a new perspective on how and why the Neolithic way of life developed through continental Europe and how dairy products became a part of the human diet.
Keywords: History, Ancient; mléko; cattle; husbandry practices; mortality profiles; Animal Husbandry; Europe; archeologie; Linearbandkeramik; Evropa; maso; dějiny starověku; skot; chov zvířat; zvířata; Humans; Meat; Cattle; Milk; Archaeology; milk; Neolithic; lidé; Animals